Characterization of four type IV pilin homologues in Stigmatella aurantiaca DSM17044 by heterologous expression in Myxococcus xanthus. - Zaigao Tan (PLoS ONE, 2013)
As prokaryotic models for multicellular development, Stigmatella aurantiaca and Myxococcus xanthus share many similarities in terms of social behaviors, such as gliding motility. Our current understanding of myxobacterial grouped-cell motilities comes mainly from the research on M. xanthus, which shows that filamentous type IV pili (TFP), composed of type IV pilin (also called PilA protein) subunits, are the key apparatus for social motility (S-motility). However, little is known about the pilin protein in S. aurantiaca. We cloned and sequenced four genes (pilA(Sa1~4)) from S. aurantiaca DSM17044 that are homologous to pilA(Mx) (pilA gene in M. xanthus DK1622). The homology and similarities among pilA(Sa) proteins and other myxobacterial homologues were systematically analyzed. To determine their potential biological functions, the four pilA(Sa) genes were expressed in M. xanthus DK10410 (ΔpilA(Mx)), which did not restore S-motility on soft agar or EPS production to host cells. After further analysis of the motile behaviors in a methylcellulose solution, the M. xanthus strains were categorized into three types. YL6101, carrying pilA(Sa1), and YL6104, carrying pilA(Sa4), produced stable but unretractable surface pili; YL6102, carrying pilA(Sa2), produced stable surface pili and exhibited reduced TFP-dependent motility in methylcellulose; YL6103, carrying pilA(Sa3), produced unstable surface pili. Based on these findings, we propose that pilA(Sa2) might be responsible for the type IV pilin production involved in group motility in S. aurantiaca DSM17044. After examining the developmental processes, it was suggested that the expression of PilA(Sa4) protein might have positive effects on the fruiting body formation of M. xanthus DK10410 cells. Moreover, the formation of fruiting body in M. xanthus cells with stable exogenous TFPSa were compensated by mixing them with S. aurantiaca DSM17044 cells. Our results shed some light on the features and functions of type IV pilin homologues in S. aurantiaca.